PERBEDAAN DENSITAS DAN KONTRAS THORAX DENGAN MENGGUNAKAN GRID DAN TANPA GRID - Asih Puji Utami; Justhika Anggriani; Anisa Nur Istiqomah (Perhimpunan Radiografer Indonesia (PARI), 2019)
ABSTRACT Thorax examination involves the projection of Posterior Anterior, Posterior Anterior and Lateral Anterior. When doing a thorax examinationin a standing position, the object must face the bucky PA or Lateral projection stand. The study aims to determine the difference between density and thorax radiograph contrast using a grid and without a grid. The study employed quantitative descriptive method. The results show that radiographs using grids had a low density and high contrast due to the grid function which absorbed scattered radiation coming out of X-ray tubes, so that the image could distinguish between soft tissue, bone and mediastinum. Whereas on a no-grid radiograph, it had high density and contrast because all the radiation coming out of the X-ray tube was absorbed by the image receptor, therefore the resulting image was too black and not optimal in distinguishing soft tissue, bone and mediastinum. In examining the thorax, it will be more optimal by using a grid, but it can also be regulated by exposure factors.